A review of the Caribbean hamlets (Serranidae, Hypoplectrus) with description of two new species - Lobel, Phillip S. (Zootaxa, 2011)
Thirteen species of the Western Atlantic genus Hypoplectrus (Serranidae) are currently recognized, two of which are described as new. Hypoplectrus maya n. sp. (Maya hamlet) is restricted to the coastal lagoon of the Meso-American Barrier Reef system in Belize. It is a solid iridescent blue, lacks nose spots and lacks black margins on fins. Hypoplectrus randallorum n. sp. (Tan hamlet) is found widely in the central and western Caribbean. Its color varies from light brown to tan and it has spots on the nose, at the base of the pectoral fin and occasionally on the upper part of the caudal peduncle. All identified species of Hypoplectrus are illustrated in live coloration along with examples of color variations in H. nigricans and H. unicolor. A historical review of Hypoplectrus is included with a discussion of issues concerning their taxonomy.